Insolvency after the 2005 bankruptcy reform - Stefania Albanesi; Jaromir Nosal (Institute for Advanced Studies (IHS), 2015)
Using a comprehensive panel data set on U.S. households, we study the effects of the 2005 Bankruptcy Abuse Prevention and Consumer Protection Act (BAPCPA), the most substantive reform of personal bankruptcy in the United States since the Bankruptcy Reform Act of 1978. The 2005 legislation introduced a means test based on income to establish eligibility for Chapter 7 bankruptcy and increased the adminis- trative requirements to file, leading to a rise in the opportunity cost and, especially, the financial cost of filing for bankruptcy. We study the effects of the reform on bankruptcy, insolvency, and foreclosure. We find that the reform caused a permanent drop in the Chapter 7 bankruptcy rate relative to pre-reform levels, due to the rise in filing costs associated with the reform, which can be interpreted as resulting from liquidity constraints. We find that the decline in bankruptcy filings resulted in a rise in the rate and persistence of insolvency as well as an increase in the rate of foreclosure. We find no evidence of a link between the decline in bankruptcy and a rise in the number of individuals who are current on their debt. We document that these effects are concentrated at the bottom of the income distribution, suggesting that the income means tests introduced by BAPCPA did not serve as an effective screening device. We show that insolvency is associated with worse financial outcomes than bankruptcy, as insolvent individuals have less access to new lines of credit and display lower credit scores than individuals who file for bankruptcy. Since bankruptcy filings declined much more for low-income individuals, our findings suggest that, for this group, BAPCPA may have removed an important form of relief from financial distress.
Keywords: 330